Nilai-nilai Pendidikan Karakter dalam Muatan Pembelajaran Bahasa Indonesia di Kelas III SDS Harapan Jakarta - Ronald Felix Yanuar; Theresia Niken Dwi Utami Putri (EDUCARE: Journal of Primary Education, 2021)
This research was carried out at SDS Harapan Jakarta. This research aims to unravel the implementation of character education’s values through thematic subject, specifically on Indonesian Language Content. This research uses qualitative descriptive approach to gather research data deeply and thoroughly regarding character education’s value. Data collection was done using interviews, observation, and documentation. Miles and Huberman method was used to analyze data collected with the process of data collection, condensation, data display, and data verification. Triangulation was used to verify the validity of the data. The result of this study revealed that 1) The implementation of character education values in the content of Indonesian Language learning in Class 3 is implemented through reading and writing activities that prioritize the five main values in education according to the Minister of Education and Culture. 2) There are still less-effective efforts to achieve learning objectives. 3) There is still a lack of learning innovations carried out to achieve learning goals. 4) No lesson plans that are not made routinely as a means of evaluating learning. 5) There is still a need for improvement in the application of character education in Indonesian content that is linked to students' real experiences, both through online and offline learning.  Keywords: Character Education; Primary School; Thematic Learning; Indonesian Language Content  Penelitian ini dilaksanakan di SDS Harapan Jakarta. Penelitian ini bertujuan untuk mengungkap implementasi nilai-nilai pendidikan karakter melalui mata pelajaran tematik, khususnya pada muatan bahasa Indonesia. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk mengumpulkan data penelitian secara mendalam dan menyeluruh mengenai nilai pendidikan karakter. Pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi. Metode Miles dan Huberman digunakan untuk menganalisis data yang dikumpulkan dengan proses pengumpulan data, kondensasi, tampilan data, dan verifikasi data. Triangulasi digunakan untuk memverifikasi keabsahan data. Hasil penelitian ini mengungkapkan bahwa 1) Implementasi nilai pendidikan karakter dalam muatan pembelajaran Bahasa Indonesia di Kelas 3 diterapkan melalui kegiatan membaca dan menulis yang mengedepankan lima nilai utama dalam pendidikan sesuai Permendikbud. 2) Masih ada upaya-upaya yang kurang efektif untuk mencapai tujuan pembelajaran. 3) Masih kurangnya inovasi pembelajaran yang dilakukan untuk mencapai tujuan pembelajaran. 4) Tidak ada RPP yang tidak dibuat secara rutin sebagai sarana evaluasi pembelajaran. 5) Masih perlu adanya perbaikan penerapan pendidikan karakter konten bahasa Indonesia yang dikaitkan dengan pengalaman nyata peserta didik, baik melalui pembelajaran online maupun offline. Kata Kunci: Pendidikan Karakter; Sekolah Dasar; Pembelajaran Tematik; Muatan Bahasa Indonesia